2019
DOI: 10.1105/tpc.19.00552
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Networks for Acylsugar Metabolism and Plant Defense in Wild Tomato Solanum pennellii

Abstract: Many solanaceous plants secrete acylsugars, which are branched-chain and straight-chain fatty acids esterified to Glu or Suc. These compounds have important roles in plant defense and potential commercial applications. However, several acylsugar metabolic genes remain unidentified, and little is known about regulation of this pathway. Comparative transcriptomics between low-and high-acylsugar-producing accessions of Solanum pennellii revealed that expression levels of known and novel candidate genes (putativel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 75 publications
4
50
0
1
Order By: Relevance
“…A group of accessions from the Nazca region, described as S. pennellii var. puberulum, are trichome-deficient and exhibit minimal accumulation of acylsugars and transcripts of genes associated with acylsugar metabolism [26,39]; our pilot experiments confirmed the absence of detectable acylsugars in this group and these accessions were excluded from this study. All extracts were analyzed by UHPLC-HR-MS using positive-mode electrospray ionization.…”
Section: Experimental Designmentioning
confidence: 52%
“…A group of accessions from the Nazca region, described as S. pennellii var. puberulum, are trichome-deficient and exhibit minimal accumulation of acylsugars and transcripts of genes associated with acylsugar metabolism [26,39]; our pilot experiments confirmed the absence of detectable acylsugars in this group and these accessions were excluded from this study. All extracts were analyzed by UHPLC-HR-MS using positive-mode electrospray ionization.…”
Section: Experimental Designmentioning
confidence: 52%
“…Together, these steps resulted in a list of 42 candidates. Previously characterized ASATs are expressed and enriched in glandular trichomes relative to non-acylsugar accumulating tissues (Schilmiller et al, 2012a; Ning et al, 2015; Fan et al, 2016; Moghe et al, 2017; Nadakuduti et al, 2017; Leong et al, 2019; Mandal et al, 2020). Thus, the 17 candidates with >500 reads in the trichome samples were selected for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…ASATs sequentially transfer acyl chains from acyl-CoAs to generate acylsucroses in plants as phylogenetically divergent as Solanum lycopersicum, Solanum pennellii, Petunia axillaris , and Salpiglossis sinuata (Schilmiller et al, 2012a; Schilmiller et al, 2015; Fan et al, 2016; Fan et al, 2017; Moghe et al, 2017; Nadakuduti et al, 2017). Expression of characterized ASATs is enriched in glandular trichomes relative to non-acylsugar producing tissues (Ning et al, 2015; Moghe et al, 2017; Nadakuduti et al, 2017; Leong et al, 2019; Mandal et al, 2020). Phylogenetic and functional analyses revealed that orthologs have similar – but distinct – substrate selectivity in acylsugar biosynthesis across the Solanaceae family (Moghe et al, 2017; Nadakuduti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…7), we assessed a putative efflux transporter, which may be responsible for acylsugar exudation in type-IV trichome tips. Notably, the ABC transporter previously associated with acylsugar exudation (Mandal et al, 2019) presented a higher expression level in S. galapagense compared to MT-Get, which correlates with the differences in their exudation capacity (Suppl. Fig.…”
Section: Figmentioning
confidence: 87%
“…7d-e) and may sustain the positive feedback responsible for AS production. Recently, a comparative transcriptomic analysis of Solanum pennellii accessions with distinct AS contents found that the expression levels of most AS metabolic genes were positively correlated with AS accumulation (Mandal et al, 2019). Among the differentially expressed genes (DEGs), three genes putatively encoding ATP-binding cassette (ABC) transporters were upregulated in the accessions with high AS content.…”
Section: Discussionmentioning
confidence: 99%